Multicomponent Strategy with Decentralized Molecular Testing for Tuberculosis - Cattamanchi, A.; Reza, T.F.; Nalugwa, T.; Adams, K.; Nantale, M.; Oyuku, D.; Nabwire, S.; Babirye, D.; Turyahabwe, S.; Tucker, A.; Sohn, H.; Ferguson, O.; et al. (New England Journal of Medicine, 2021)
Effective strategies are needed to facilitate the prompt diagnosis and treatment of tuberculosis in countries with a high burden of the disease. METHODS We conducted a cluster-randomized trial in which Ugandan community health centers were assigned to a multicomponent diagnostic strategy (on-site molecular testing for tuberculosis, guided restructuring of clinic workflows, and monthly feedback of quality metrics) or routine care (on-site sputum-smear microscopy and referral-based molecular testing). The primary outcome was the number of adults treated for confirmed tuberculosis within 14 days after presenting to the health center for evaluation during the 16-month intervention period. Secondary outcomes included completion of tuberculosis testing, same-day diagnosis, and sameday treatment. Outcomes were also assessed on the basis of proportions. RESULTS A total of 20 health centers underwent randomization, with 10 assigned to each group. Of 10,644 eligible adults (median age, 40 years) whose data were evaluated, 60.1% were women and 43.8% had human immunodeficiency virus infection. The intervention strategy led to a greater number of patients being treated for confirmed tuberculosis within 14 days after presentation (342 patients across 10 intervention health centers vs. 220 across 10 control health centers; adjusted rate ratio, 1.56; 95% confidence interval [CI], 1.21 to 2.01). More patients at intervention centers than at control centers completed tuberculosis testing (adjusted rate ratio, 1.85; 95% CI, 1.21 to 2.82), received a same-day diagnosis (adjusted rate ratio, 1.89; 95% CI, 1.39 to 2.56), and received same-day treatment for confirmed tuberculosis (adjusted rate ratio, 2.38; 95% CI, 1.57 to 3.61). Among 706 patients with confirmed tuberculosis, a higher proportion in the intervention group than in the control group were treated on the same day (adjusted rate ratio, 2.29; 95% CI, 1.23 to 4.25) or within 14 days after presentation (adjusted rate ratio, 1.22; 95% CI, 1.06 to 1.40). CONCLUSIONS A multicomponent diagnostic strategy that included on-site molecular testing plus implementation supports to address barriers to delivery of high-quality tuberculosis evaluation services led to greater numbers of patients being tested, receiving a diagnosis, and being treated for confirmed tuberculosis. (Funded by the National Heart, Lung, and Blood Institute; XPEL-TB ClinicalTrials.gov number, NCT03044158.)
Keywords: Multicomponent Strategy; Molecular Testing; Tuberculosis